Black educational leadership : from silencing to authenticity - Rogers-Ard, Rachelle, 1965-; Knaus, Christopher Bodenheimer (New York, NY : Routledge, 2021)
"This book explores Black educational leadership and the development of anti-racist, purpose-driven leadership identities. With a focus on thirteen leaders, this volume demonstrates how US schools exclude African American students, and the impacts such exclusions have on Black school leaders. It clarifies parallel racism along the pathway to becoming teachers and school leaders, framing an educational pipeline designed to silence and mold educators into perpetrators of educational disparities. This book is designed for district administrators as well as faculty and students in Race and Ethnicity in Education, Urban Education, and Educational Leadership"--
Foreword: Black leadership in the uncertain time of now -- Black leadership within anti-black schools -- This is who we are -- But I don't want to be a principal : intersectional racism and black leadership pathways -- They don't see our babies -- They don't see me : coping and the double duty of authenticity -- This is how we do : authentic leadership -- Epilogue: Where are they now?
OCLC-licensed vendor bibliographic record.
Keywords: African American school administrators; African American school administrators -- Anecdotes; African American students -- Social conditions; Educational leadership -- United States; Racism in education -- United States; Discrimination in education -- United States; EDUCATION / General